2007
DOI: 10.1097/01.aog.0000262054.03531.24
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Significance of Isolated Maternal Hypothyroxinemia Identified in the First Half of Pregnancy

Abstract: Isolated maternal hypothyroxinemia has no adverse effects on perinatal outcome. Moreover, unlike subclinical hypothyroidism, there was a low prevalence of thyroid peroxidase antibodies and no correlation between TSH and free T(4) levels in women with hypothyroxinemia, leading us to question its biological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
156
3
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(191 citation statements)
references
References 17 publications
16
156
3
11
Order By: Relevance
“…Interestingly, in a very recent study by Henrichs et al [44] carried out in The Netherlands on a cohort of 3659 women, the prevalence of mild hypothyroxinemia (FT4 < 10th percentile) was 8.5% and that of severe hypothyroxinemia (FT4 < 5th percentile) 4.3%. These figures are significantly higher than those reported in previous studies conducted in iodine sufficient regions [40,42].…”
Section: Epidemiologycontrasting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, in a very recent study by Henrichs et al [44] carried out in The Netherlands on a cohort of 3659 women, the prevalence of mild hypothyroxinemia (FT4 < 10th percentile) was 8.5% and that of severe hypothyroxinemia (FT4 < 5th percentile) 4.3%. These figures are significantly higher than those reported in previous studies conducted in iodine sufficient regions [40,42].…”
Section: Epidemiologycontrasting
confidence: 80%
“…In another study, risks of adverse pregnancy outcomes were not increased in over 200 pregnant women with isolated hypothyroxinemia [40].…”
Section: Isolated Maternal Hypothyroxinemiamentioning
confidence: 95%
See 1 more Smart Citation
“…Multiple studies have reported an association of SCH with an increase in the risk of adverse pregnancy and neonatal outcomes, including pregnancy loss, preterm delivery, gestational diabetes, gestational hypertension, preeclampsia, placental abruption, premature rupture of membranes, intrauterine growth restriction, low birth weight, small for gestational age, low Apgar score, and neonatal death (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Furthermore, high TSH levels in women during pregnancy have been associated with an increased risk of neurocognitive deficits in the offspring (17).…”
mentioning
confidence: 99%
“…[8][9][10][11] However, the risks of these adverse outcomes are not increased among women with hypothyroxinemia in pregnancy. 12,13 These findings led several professional organizations to recommend routine prenatal screening for and treatment of subclinical thyroid disease during pregnancy. 14 This recommendation could affect more than 15% of pregnant women, depending on the thyrotropin and free T 4 thresholds used.…”
mentioning
confidence: 99%